The Deployment of Routing Protocols in Distributed Control Plane of SDN. (27th August 2014) - Jingjing, Zhou; Di, Cheng; Weiming, Wang; Rong, Jin; Xiaochun, Wu
Abstract : Software defined network (SDN) provides a programmable network through decoupling the data plane, control plane, and application plane from the original closed system, thus revolutionizing the existing network architecture to improve the performance and scalability. In this paper, we learned about the distributed characteristics of Kandoo architecture and, meanwhile, improved and optimized Kandoo's two levels of controllers based on ideological inspiration of RCP (routing control platform). Finally, we analyzed the deployment strategies of BGP and OSPF protocol in a distributed control plane of SDN. The simulation results show that our deployment strategies are superior to the traditional routing strategies.